Introduction to the practitioners' special section: Financing the green transition in times of crisis - Mariane Søndergaard-Jensen; Andreas Klasen (Global Policy, 2022)
Making innovation, trade, investment and environment policy goals mutually supportive creates challenges for internationally-oriented firms, financial institutions, governments and other stakeholders. Will the Ukraine war derail the green energy transition? How can governments and the financial system work together to broaden, deepen, and accelerate the global transition to net-zero? What are innovation, trade and investment opportunities for green growth? How to refocus government financing instruments to support countries and trade partners meet their climate targets in times of crisis? The IfTI Global Symposium 2022 hosted by the Institute of Trade and Innovation (IfTI) at Offenburg University discussed challenges to trade in a new global order, as well as opportunities and threats of the green transition. This Special Section brings together practitioner commentaries of key symposium speakers.
Keywords: 320